Diseño e implementación de un módulo didáctico para el aprendizaje y operación de controladores lógicos programables, monitoreado mediante el software intouch en el laboratorio de electromecánica de la Universidad Técnica de Cotopaxi, extensión La Maná, año 2015 - Moreno Peñafiel, Elvis Patricio (2016)
This project is aimed to the construction of a training module for learning and operation of programmable logic controllers, monitored by Intouch software and Step S7 1200 PLC for Electromechanics Laboratory. With the implementation of the training module the student of Engineering in Electromechanics will be able to make their labs to acquire a knowledge of the functioning and operation of PLCs.